Fabrication of Alkaline Earth Oxide-Containing Glass Adsorbents for Capturing Carbon Dioxide under Mild Conditions. (July 2022) - Kim, Hyung-Ju; Kim, Sung-Jun; Yang, Hee-Chul; Eun, Hee-Chul; Lee, Keunyoung; Lee, Jung-Hyun
Abstract: With growing global concern on radiological hazards, there has been strong interest in the adsorbents for the treatment of radioactive carbon dioxide (CO2 ) containing C-14, which should be removed under mild operating conditions. In this study, we fabricated a new class of alkaline earth oxide-containing glass adsorbents with high CO2 adsorption capacity and good adsorption rate under mild aqueous conditions, which is not feasible with alkaline earth oxide-containing natural minerals. The glass adsorbents were fabricated by incorporating alkaline earth oxides (SrO or CaO) into an amorphous glass framework using network modifiers (Na2 O or K2 O). The comprehensive characterization of the structure and adsorption and dissolution properties of the fabricated glass adsorbents revealed that CO2 was adsorbed via the dissolution of alkaline earth metal ions and their subsequent carbonation through heterogeneous surface nucleation. Variation in the type of alkaline earth metals and network modifiers significantly affected the CO2 adsorption performance and kinetics of the glass adsorbents by altering the dissolution behavior of the alkaline earth metal ions. The best fabricated glass adsorbent exhibited a high maximum CO2 capacity of 5.56 mmol g −1 and a fast carbonation rate of 5.31 mmol g −1 h −1 in deionized water under ambient conditions, demonstrating its potential application in treating radioactive CO2 . Graphical Abstract: ga1 Highlights: A new class of CO2 adsorbents are fabricated based on amorphous glass structure. The fabricated glass adsorbent enhances the rate of dissolution and carbonation under mild conditions. The glass adsorbents exhibit CO2 capacity of 4.43–5.11 mmol g −1 with rapid carbonation rate of 4.09–4.25 mmol g −1 h −1 . The network modifier with a larger ionic radius results in a higher carbonation rate and greater CO2 capacity. The performances of the recent developments on mineral carbonation technology are surveyed.